Perancangan Turbin Pelton untuk Pembangkit Listrik Tenaga Air - Normansyah Normansyah (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
In developing countries the necessity and the possibilities to manufacture machines locally are inc!easing. Often be necessary equipment, machines, material and the skilled labour as well as technical staff are available, but what is missing is the information and the know-how. One category of machines used to harness walet power and which can be produced locally, are water turbines. In some countries there is an established tradition in the production, installing and running of small water mills. Often these are units with simple vertical axis wheels or are large water wheels. For example, one country with experience on vertical axis water wheels.This research summarizes the simple calculations for designing a Pelton turbine with a head of water falling of 1130 m, with a discharge of Q = 28.5 m3/s, so that based on the calculations, a power of P = 288 MW is obtained.